2019
DOI: 10.1021/acssuschemeng.8b05835
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of an Antifouling Surface Modification on the Environmental Impact of a Pasteurization Process: An LCA Study

Abstract: As concerns grow about the sustainability of current food production patterns, it is important to assess their environmental impact, to identify the hotspots, and to propose curative solutions in order to progress toward more durable and ecofriendly production processes. Dairy products are a significant part of the human diet, but their production is responsible for substantial emission of pollutants such as greenhouse gases and fine particles. Following a life cycle assessment (LCA) approach, this study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Water scarcity was assessed using the AWARE method 24 . Because the production of Tr-OVA is an industrial food manufacturing process relying on electricity and natural gas, we included impact categories that are commonly used for both agricultural and industrial food manufacturing LCA studies 18,[25][26][27][28] . Because of the industrial nature of the product, the life cycle industrial energy use was also assessed using the cumulative energy demand (CED) V1.1 method by ecoinvent 29 .…”
Section: Goal and Scope Of The Lca Studymentioning
confidence: 99%
“…Water scarcity was assessed using the AWARE method 24 . Because the production of Tr-OVA is an industrial food manufacturing process relying on electricity and natural gas, we included impact categories that are commonly used for both agricultural and industrial food manufacturing LCA studies 18,[25][26][27][28] . Because of the industrial nature of the product, the life cycle industrial energy use was also assessed using the cumulative energy demand (CED) V1.1 method by ecoinvent 29 .…”
Section: Goal and Scope Of The Lca Studymentioning
confidence: 99%
“…This would reduce cleaning cost up to 35%. To go further, in a life cycle assessment study, Zouaghi et al (2019) demonstrated that repeated CIP burdens the environmental footprint of the pasteurization process. They pointed out that surface modification leading to clean surfaces with water only (no need of detergents) reduces the environmental impact of the pasteurization process by more than 70%.…”
Section: Cleaning Conditions Referencesmentioning
confidence: 99%
“…The coating system used to increase the anti-fouling properties of the process has been identified as the most important contributor in terms of environmental impact. This is due to many solvents and oil-based chemicals used to synthesize the coating (Zouaghi et al, 2019).…”
Section: Total Environmental Impact Of Each Processmentioning
confidence: 99%
“…Indeed, several LCAs in the coating field have been conducted, however dealing with other applications than fire protection. For example, the environmental impact of antifouling coatings in marine (Rossini et al, 2019) and food engineering (Zouaghi et al, 2019) was investigated. Both reports demonstrate that the production step of antifouling coating significantly affects the environmental impact of the system due to the chemicals used.…”
Section: Introductionmentioning
confidence: 99%